Meta-analysis of nursing effect of enhanced recovery after surgery in patients after laparoscopic hepatectomy (加速康复外科护理对腹腔镜肝切除术后患者护理效果的Meta分析) - LI Mimi (李咪咪); ZHOU Hui (周慧); CHEN Yanyan (陈艳艳); SONG Rui (宋睿); HAO Yuying (浩育盈) (中西医结合护理)
Objective To systematically evaluate the effect of enhanced recovery after surgery (ERAS) for patients undergoing laparoscopic hepatectomy. Methods Studies on the effect of ERAS-based nursing interventions for patients undergoing laparoscopic hepatectomy were retrieved fromCNKI, Wanfang database, VIP database, Chinese Biomedical Literature Database (CBM), PubMed, Embase, Web of Science database from the establishment to September 2024. Two trained researchers extracted relevant information according to the inclusion and exclusion criteria, and conducted the Meta-analysis using Revman5. 2 software. Results A total of 10 literature articles were included, containing 1, 093 patients. Of these, 528 patients were included in the ERAS group and 565 cases were included in the control group. As shown by the Meta-analysis, there were significant difference in length of hospital stay ［MD= -3. 55, 95%CI(-4. 90, -2. 19), P＜0. 01］, time to the extubation ［MD= -1. 31, 95%CI(-1. 70, -0. 93), P＜0. 01］, eating time ［MD= -8. 42, 95%CI(-10. 21, -6. 63), P＜0. 01］, time of first anal exhaust ［MD= -3. 92, 95%CI(-4. 84, -3. 01), P＜0. 01］, time of first defecation ［MD= -1. 84, 95%CI(-2. 74, -0. 94), P＜0. 01］, Self-rating Anxiety Scale (SAS) score ［MD= -5. 69, 95%CI(-6. 53, -4. 86), P＜0. 01］, pain Visual Analogue Scale(VAS) score ［MD= -1. 38, 95%CI(-1. 82, -0. 94), P＜0. 01］, complication rate ［RR=0. 37, 95%CI(0. 17, 0. 82), P＜0. 05］, satisfaction with care ［RR=1. 28, 95%CI(1. 10, 1. 50), P＜0. 05］ between ERAS group and control group. Conclusion For patients undergoing laparoscopic hepatectomy, the ERAS can shorten the hospital stay, extubation time and eating time, advance the first anal exhaust time and the first defecation time, reduce the SAS score and VAS score, reduce the complication rate, and improve the nursing satisfaction. (目的 系统评价对腹腔镜下肝切除患者实施加速康复外科护理的效果。方法 计算机系统检索知网(CNKI)、万方数据库(Wanfang Data)、维普数据库(VIP)、中国生物医学文献数据库(CBM)、PubMed、Embase、Web of Science数据库, 搜索关于加速康复外科对腹腔镜肝切除护理效果的随机对照研究相关文献, 建库至2024年9月, 使用Revman5. 2软件进行Meta分析。结果 共纳入10篇文献, 共计1093例患者, 其中观察组(ERAS护理干预)528例, 对照组(常规护理干预)565例。通过Meta分析显示, 加速康复外科和常规护理式在住院时间［MD=-3. 55, 95%CI(-4. 90, -2. 19), P＜0. 01］、拔管时间［MD=-1. 31, 95%CI(-1. 70, -0. 93), P＜0. 01］、进食时间［MD=-8. 42, 95%CI(-10. 21, -6. 63), P＜0. 01］、首次肛门排气时间［MD=-3. 92, 95%CI(-4. 84, -3. 01), P＜0. 01］、首次排便时间［MD=-1. 84, 95%CI(-2. 74, -0. 94), P＜0. 01］、焦虑自评量表(SAS)评分［MD=-5. 69, 95%CI(-6. 53, -4. 86), P＜0. 01］、疼痛视觉模拟量表(VAS)评分［MD=-1. 38, 95%CI(-1. 82, -0. 94), P＜0. 01］、并发症发生率［RR=0. 37, 95%CI(0. 17, 0. 82), P＜0. 05］、护理满意度［RR=1. 28, 95%CI(1. 10, 1. 50), P＜0. 05］方面比较, 差异有统计学意义。结论 加速康复外科的应用能够缩短腹腔镜肝切除术后患者住院时间、拔管时间以及进食时间, 提前首次肛门排气时间以及首次排便时间, 降低SAS评分、VAS评分, 减少并发症发生率, 提高护理满意度。)